Tax Knowledge, Financial Reward, and Labor Market on Career Choice: Pengetahuan Pajak, Insentif Keuangan, dan Pasar Tenaga Kerja terhadap Pilihan Karier - Masfufah , Ninik; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2025)
Background: Tax profession is an important career field due to the growing need of taxation personnel, yet students’ interest remains low. Specific Background: Previous studies examined single variables, while the combination of tax knowledge, financial reward, and labor market consideration has not been widely tested in the Indonesian accounting context. Gap: Evidence regarding students’ career preference in taxation that integrates those three aspects is still limited. Aim: This study examines the effect of tax knowledge, financial reward, and labor market consideration on accounting students’ career choice in taxation. Results: The regression analysis shows that all independent variables have a positive and significant effect on career choice. Novelty: The research provides empirical evidence that these three constructs jointly shape students’ decision for taxation careers, particularly in the Muhammadiyah University context. Implications: The findings suggest universities should improve taxation learning experience and institutions may consider incentive and employment information to strengthen future taxation workforce. Highlights:• Significant role of tax knowledge• Importance of financial reward• Labor market relevance Keywords: Tax Knowledge, Financial Reward, Labor Market, Career Choice, Accounting Students